Clinical characteristics and outcomes of macrophage activation syndrome among patients attending a rheumatology tertiary care center in North India - Rasmi Ranjan Sahoo; Manesh Manoj; Prashant Bafna; Kasturi Hazarika; Anupam Wakhlu (Indian Journal of Rheumatology)
Background: Macrophage activation syndrome (MAS) is a potentially fatal condition complicating several rheumatologic disorders. This retrospective analysis studied the clinical characteristics and outcomes of patients diagnosed with MAS from a rheumatology tertiary care center. Methods: Pediatric and adult patients diagnosed with rheumatologic disorders and fulfilling the 2016 European League against Rheumatism/American College of Rheumatology classification criteria for MAS associated with systemic juvenile idiopathic arthritis (sJIA) or the hemophagocytic lymphohistiocytosis (2004) criteria, as appropriate, were included over a period of 1 year. Detailed clinical history and laboratory parameters were extracted from the patients' records. Treatment details, duration of hospitalization, and outcomes were recorded. Results: The study included nine patients (five males and four females) with a median age of 27 years, range 10–48 years. The median duration of illness was 6 months, range 2–60 months. Five patients were diagnosed with systemic lupus erythematosus, two patients with adult-onset Still's disease, and one each with sJIA and sarcoidosis. Infection (three patients), malignancy (one patient), and uncontrolled or aggressive disease (five patients) were recognized as the possible precipitating factors. Three patients had pancytopenia at presentation, whereas bicytopenia was observed in five patients. Hemophagocytosis on bone marrow biopsy was seen in seven patients. The median duration of hospital stay was 3 weeks, range 2–4 weeks. High-dose steroids were administered to all patients, along with oral cyclosporine in seven patients. One patient was given weekly etoposide infusion for unabated MAS. Two patients expired. Conclusion: Prompt diagnosis and aggressive treatment strategy are pivotal for improving prognosis in MAS complicating rheumatologic disorders.